1987
DOI: 10.3109/03009748709165414
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Biopsy from Subcutaneous Fat: An Easy Way to Diagnose Secondary Amyloidosis

Abstract: Secondary amyloidosis is usually diagnosed by demonstrating amyloid deposits on histological sections by Congo red staining. An alternative method is a fine needle aspiration biopsy (FNAB) from subcutaneous fat which, in this study, was carried out on 301 patients. In order to test the efficiency of FNAB we analysed 146 patients from whom in addition to FNAB one or two histological samples including 125 oral and 65 rectal biopsies were available. FNAB proved very reliable for demonstrating secondary amyloidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
4

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 11 publications
1
24
0
4
Order By: Relevance
“…4 Previous studies in the literature on diagnostic efficacy of FNAC of fat pad have reported sensitivities of 55-82%. 2,3,[6][7][8][9] The sensitivity (78%) of our study group is comparable to that of others, especially to that of Klemi et al, 6 who reported a high sensitivity of 82%. A negative FNAC of fat pad does not necessarily indicate the absence of systemic amyloidosis.…”
Section: Discussionsupporting
confidence: 78%
“…4 Previous studies in the literature on diagnostic efficacy of FNAC of fat pad have reported sensitivities of 55-82%. 2,3,[6][7][8][9] The sensitivity (78%) of our study group is comparable to that of others, especially to that of Klemi et al, 6 who reported a high sensitivity of 82%. A negative FNAC of fat pad does not necessarily indicate the absence of systemic amyloidosis.…”
Section: Discussionsupporting
confidence: 78%
“…To detect amyloid deposits in tissues, alkaline Congo red staining has been commonlyemployed in previous studies involving histopathological examinations (13,14,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Using this method several reports have shownpositive rates of 50-60%in abdominal fat tissue and 80-^-90% in gastroduodenal and rectal mucosa in patients with systemic reactive AAamyloidosis (1,13,14,16,22). In the present study with abdominal fat tissues the alkaline Congored staining showed a positive result in 70% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the histopathological diagnosis of reactive AA amyloidosis either the gastroduodenal and rectal mucosa or abdominal fat tissue has been commonly used as a biopsy site (1,(12)(13)(14)(15)(16)(17)(18). A few reports have shown that the bulbus and the second portion of the duodenumare the most sensitive site for biopsy (15,16), but an endoscopic examination is often difficult and risky in RApatients, particularly in those with either various complications, including ischemic heart disease, or involvement of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%